Yurisprudensi Hukum Pencegahan Perkawinan melalui Putusan Pengadilan (Studi Putusan Nomor 32/Pdt.P/2019/PA.Bn) - Nasution, Muhammad Iqbal Hanafi; Sukiati, Sukiati; Harahap, Muhammad Yadi (Lembaga Yasin AlSys, 2025)
This study is motivated by the absence of social considerations, such as long distance marriage, as a valid legal basis for marriage prevention under positive law, despite empirical evidence indicating that such conditions often lead to marital issues. The aim of this research is to analyze Decision Number 32/Pdt.P/2019/PA.Bn concerning a marriage prevention petition filed by a father against his daughter’s prospective husband on the grounds of kafa’ah incompatibility and the risks associated with a long-distance marriage. The method employed is normative juridical, using a case law approach and a conceptual review of Islamic legal principles and Indonesian legal regulations, particularly Law Number 1 of 1974 and the Kompilasi Hukum Islam (KHI). The findings show that the Panel of Judges rejected the petition on the grounds that the reasons presented did not meet the formal legal requirements as stipulated in Article 13 of the Marriage Law and Article 60 of the KHI. The panel adhered to the principle of legality and ruled that long distance marriage and kafa’ah incompatibility cannot serve as legal grounds for preventing a marriage. Nevertheless, from a social and jurisprudential perspective, long-distance marriages have frequently been identified as contributing factors to divorce in various religious court decisions. The study concludes that although social reasons such as long distance marriage have tangible impacts, they are not yet normatively recognized within Indonesia’s marriage law framework. The implication is a need for regulatory reformulation and more adaptive interpretative approaches to social realities, along with the strengthening of premarital counseling programs and labor policies that support family cohesion.